Elemental analysis of mosses and lichens from the Western Cape (South Africa) using INAA and ICP-MS - Ndlovu, Ntombizikhona Beaulah (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil)--Stellenbosch University, 2016